Association of rs12722 COL5A1gene variation with risk of anterior cruciate ligament rupture - V. Pushkarev; D. Dyatlov; R. Akhmetyanov; A. Chmutov; Y. Pushkareva; L. Pollyak (National Electronic Information Consortium (NEICON), 2020)
Objective: to determine the influence of rs12722 (C/T)COL5A1 gene variation on ACL rupture in Europeans of Ural region of Russia. Materials and methods: the case group included 173 patients with diagnosed anterior cruciate ligament (ACL) ruptures; control group included 370 asymptomatic persons. Both groups were similar on a sex, age, growth, weight and BMI. Results: the following genotypic frequencies were observed (in %): case group - a T/T of 34,1, C/T of 46,8, C/C of 19,1; control group - a T/T of 25,4, C/T of 50,8, C/C 23,8. Genotypic frequencies in both groups met Hardy-Weinberg equilibrium. Significant difference of allelic frequencies was revealed between two groups (p = 0,039). Persons with a T/T genotype had a significantly increased risk of ACL ruptures in comparison with persons with C/T + C/C genotypes (x2 = 4,408, p = 0,036, OR = 1,52, 95% confidence interval: 1,027 - 2,249). Conclusions: this is the first study that shown the association of rs12722 COL5A1 gene variation with risk of an ACL rupture in Russian population.